2011
DOI: 10.2106/jbjs.i.01753
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Comparison of Oxidized Zirconium and Cobalt-Chromium Femoral Components in Total Knee Arthroplasty

Abstract: Five-year outcomes after total knee arthroplasty with oxidized zirconium and cobalt-chromium femoral components showed no significant differences in clinical, subjective, and radiographic outcomes. Patients had no preference or preferred the cobalt-chromium prosthesis to the oxidized zirconium prosthesis at the time of the five-year follow-up. There were no adverse effects associated with the use of oxidized zirconium femoral implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 24 publications
2
34
0
2
Order By: Relevance
“…Because of their lack of a comparable sample with a different bearing type, no estimation of risk could be made. In the randomized controlled trial published by Hui et al (2011), which involved 40 patients and 80 knees (1 with CoCr and 1 with OZ femoral components), no differences in clinical, subjective, or radiographic outcomes were found 1, 2, and 5 years postoperatively. 2 patients (4 knees) were revised in this study during the follow-up (corresponding to a revision rate of 3% for each femoral component type) and no differences in wear pattern were reported in the retrieved components.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Because of their lack of a comparable sample with a different bearing type, no estimation of risk could be made. In the randomized controlled trial published by Hui et al (2011), which involved 40 patients and 80 knees (1 with CoCr and 1 with OZ femoral components), no differences in clinical, subjective, or radiographic outcomes were found 1, 2, and 5 years postoperatively. 2 patients (4 knees) were revised in this study during the follow-up (corresponding to a revision rate of 3% for each femoral component type) and no differences in wear pattern were reported in the retrieved components.…”
Section: Discussionmentioning
confidence: 92%
“…2 case series (Laskin 2003, Innocenti et al 2010) and 1 randomized control trial (Hui et al 2011) have been published evaluating the short- to medium-term survival of OZ femoral components. In the study by Innocenti et al (2010), younger, healthier, more active patients were selected to receive the OZ implants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a retrieval study revealed less surface damage on UHMWPE components that articulated against OxZr than components paired with CoCr [12]. Several series have compared OxZr TKA components with conventional bearing surfaces [14,17,18]; however, superiority of OxZr has not been demonstrated in terms of better implant survival, at least at midterm followup.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of synovial fluids and evaluation of amount and size of PE particles showed no differences between OxZr and CoCr femoral components [9,14].…”
Section: Discussionmentioning
confidence: 91%